Sei sulla pagina 1di 27

I R + = [0, +) I f : I −→ C

f s C t −→ e st f (t) R +

+

0

|e st f (t)|dt < +.

+

0

e st f (t) dt.

s = s 0 e st f (t) R + s C Re(s) > Re(s 0 )

|e st f(t)| = e Re(s) t |f(t)| ≤ e Re(s 0 ) t |f(t)| = |e s 0 t f(t)|,

e st f (t)

s C +e st f (t) dt

0

s

σ = Re(s) > σ[f],

σ[f ] s C

+

0

e st f (t) dt

f : I −→ C R + I

σ[f ] := inf Re(s) : e st f (t) ,

s Re(s) > σ[f ] f

L[f ](s) = F (s) := +e st f (t) dt.

0

σ[f ] f

f (t) α

|f(t)| ≤ M e α t

α R

σ[f ] α s C Re(s) > α

|e s t f(t)| = e Re(s) t |f(t)| e Re(s) t M e α t = Me (αRe(s))t

R +

α = 0

|f (t)| ≤ M

H(t) =

  t 0

1

0

e s t R +

|e s t | = e Re(s) t

R + Re(s) > 0

σ[f ] = 0

L[H](s) = +e st dt = 1

0

s .

1 s C= C\ {0}

Re(s) > 0 H(t)

f (t) = e at a = α +i β t −→ e st e at = e (sa)t

Re(s a) = Re(s) α > 0 Re(s) > α

σ[f ] = α

L[f ](s) = +

0

e (sa)t dt =

1

s a .

a = 0

h > 0

X [0,h) (t) = H(t) H(t h) =


1

0

0 t < h

s

= 0

L[X [0,h) ](s) = +e st X [0,h) (t) dt = h e st dt = e st

0

0

s

t=0

t=h

= 1 e sh s

.

s = 0

s0 L[X [0,h) ](s) = lim

lim

s0

1 e sh

s

= lim

s0

1 e sh

sh

h = h = L[X [0,h) ](0).

σ[f ] = −∞

f = 0

h > 0

δ h (t) = X [0,h) h (t)

.

R δ h (t) dt = +δ h (t) dt = 1.

0

L[δ h ](s) = 1 hs e hs

s

h0 lim L[δ h ](s) = 1.

h =

1

n , n N δ n (t)

1

n+δ

lim

n (t) =

1

0

+

t

= 0

t = 0,

[0, +]

δ(t) =

0

+

t

= 0

t = 0

δ L[δ(t)] := lim n+ L[δ n (t)] = 1.

1

f 1 f 2

σ[f 1 ] σ[f 2 ]

c 1 c 2

L[c 1 f 1 + c 2 f 2 ](s) = c 1 L[f 1 ](s) + c 2 L[f 2 ](s),

s :

Re(s) >

L[e ± iωt ](s) =

1 iω

s

max {σ[f 1 ], σ[f 2 ]} .

ω R,

Re(s) > 0.

L[sin(ωt)](s) =

2i s

1

1

s + =

1

ω s 2 +

ω 2

Re(s) > 0

s

L[cos(ωt)](s) = s 2 + ω 2

Re(s) > 0,

L[sin(t)](s) =

1 + 1

s

2

L[cos(t)](s) =

s + 1

s

2

Re(s) > 0.

1

L[e ωt ](s) = s ω

1

L[e ωt ](s) = s + ω

w R,

Re(s) > ω,

w R,

Re(s) > ω.

Re(s) > |ω|

sinh(ωt) =

e ωt e ωt

2

cosh(ωt) =

e ωt + e ωt

2

L[sinh(ωt)](s)

=

L[cosh(ωt)](s)

=

L[sinh(t)](s) =

1 1

s

2

1

2 s ω

1

s

s 2 ω 2 ,

s + ω =

1

L[cosh(t)](s) =

s 1 ,

s

2

ω s 2 ω 2

Re(s) > 1.

f

σ[f ] σ 0 > σ[f ] F (s) = L[f ](s)

Re(s) σ 0

Re(s)+F(s) = 0.

lim

{s n }

σ 0 σ n := Re(s n ) −→ +

n+ F(s n ) = 0.

lim

f

σ[f ] F (s) = L[f ](s)

Re(s) > σ[f ] t −→ −tf (t)

σ[f ]

F (s) = L[tf (t)](s),

F (s)

F (n) (s) = L[(t) n f (t)](s) = (1) n L[t n f (t)]

Re(s) > σ[f ].

f (t) t 0 f (t)

R

f + (t) =

f(t)

  0

t 0

,

f + (t) = H(t) f (t) L[f ](s) = L[f + ](s)

t < 0

t −→ t n + ,

t + 0 H(t)

= 1

n

N

n = 0 t 0

L[t + 0 ](s) = 1 s

Re(s) > 0.

n > 0

L[t n + ](s) = +e st t n dt = e st

0

s

t n t=+

t=0

+ n +

0

=

n L[t n1 ](s).

s

+

L[t + ](s) = 1 2

s

L[t + 2 ](s) = 2

s

3

L[t n + ](s) = s n+1 n!

Re(s) > 0.

e

st

s

t n1 dt =

f

• L[f (ct)](s) = 1 c L[f (t)] s c

• L[f(t t 0 )](s) = e t 0 s L[f (t)](s)

• L[e at f (t)](s) =

L[f (t)](s a)

f (t) = sen + (t)

c > 0 :

Re(s) > cσ[f ]

t 0 > 0 :

Re(s) > σ[f]

a C :

Re(s) > σ[f ] + Re(a)

[ f ] ∀ a ∈ C : Re ( s ) > σ [ f

f (t) = sen + (t π)

L[sen + (t π)] = e π s

1

s 2 + 1

sin t [0, π]

L[sin + (t)] + L[sen + (t π)] = 1 s + 2 + e π 1 s

.

s = ± i σ [ f ] = −∞ f t ≥ 0 T

s = ±i

σ[f ] = −∞

f t 0 T

f (t + T ) = f (t)

t 0

f

[0, T ]

L[f ](s) =

e Ts T

1

0

1

e st f (t) dt

Re(s) > 0.

f(t) =

2n t 2n + 1,

1

 

0

n 0

t 0 2

L [ f ( t )]( s ) = = 1 1 − 1 e

L[f (t)](s)

=

=

1

1

1

e 2s

1

1

0

s

1 +

e s

e st dt =

1

1 e s s

1 e 2s

Re(s) > 0.

=

f(t) =

  

 

1

1

0

2n t 2n + 1,

n 0

2n + 1 < t < 2n + 2,

n 0

L[f (t)](s)

=

=

=

=

=

L [ f ( t )]( s ) = = = = = e − 2

e 2s 2

1

0

1

e st f (t)dt =

e 2s 1

1

0

1

e 2s e st

1

1

s

t=1

t=0 e st

s

t=2

t=1 =

e st dt 2 e st dt =

1

1 1 e 2s 1 s (e s

+ 1) + 1 s (e 2s e s ) =

1 1 e 2s 1 s (e 2s 2e s + 1) =

1 1 e 2s 1 s (1 e s ) 2 = 1 e s

s(1 + e s ) .

2π

f(t) =


sin(t)

2t (2k + 1)π,

0

k 0

L [ f ]( s ) = = 1 1 − e − 2 πs

L[f ](s)

=

=

1

1 e 2πs

π

0

e st sin(t)dt =

1

1

1 e πs s 2 + 1 .

1

1 + e πs s 2 + 1

1 e 2πs

=

L[sin + (t)+ sin + (t π)](s)

π f (t) = |sin(t)| +

( t − π )]( s ) π f ( t ) = | sin (

L[|sin| + ](s) =

e πs π

1

0

1

e st sin(t)dt =

1

1 + e πs

1 e πs s 2 + 1 .

f t 0

s

Re(s) > max σ[f], σ[f ]

L[f ](s) = s L[f ](s) f (0).

f C 1

f

L[f ](s) = s L[f ](s) f (0) = s [s L[f ](s) f (0)] f (0) =

= s 2 L[f ](s) sf (0) f (0).

f C n1 (n 1)

L[f (n) ](s) = s n L[f ](s) s n1 f (0) + s n2 f (0) + · · · + f (n1) (0) .

y + y = 0

  y (0) = 1

y(0) = 0

Y (s) = L[y](s)

L[y + y](s) = s 2 Y (s) s y(0) y (0) + Y (s) = Y (s) (s 2 + 1) 1 = 0,

Y (s) =

1

s 2 + 1

y(t) = sin(t)

f g R

f g

(f g) (x) := R f (t) g(x t) dt.

f g

(f g) (x) =

x

0

0

f (t) g(x t) dt

x > 0

(f

g) (x) =

(g f ) (x)

 

((f

g) h) (x) = (f

(g h)) (x)

(f

(g + h)) (x) = (f

g) (x) + (f

h) (x)

f g

σ[f ] σ[g] (f g)

Re(s) > max {σ[f ], σ[g]}

L[f g](s) = L[f ](s) · L[g](s).

f σ[f ]

F (s)

(f

H)(t) = (H

f )(t) =

0

t

f (τ )

f

t > 0.

L[H f ](s) = F(s) ,

s

Re(s) > max {0, σ[f ]} .

f s

f (t) = t n1 t n

n

+

+

L t n (s) = 1 s L[t n1 ](s)

+

n

+

=

L t n (s) = n

s

+

n

L t n1

+

n

(s).

δ h (t) = X [0,h) (t) , h > 0

h

R δ h (t) = 1

h > 0

L[δ h ](s) = 1 sh e sh

.

f h (t) t 0

f h (t) = t

0

X [0,h) (τ)

h

=

  

 

 

1

t

h

t > h

t h

L[f h ](s) = 1 hs e hs

1

s ,

Re(s) > 0.

f

F

f F (s)

σ[f ]. α > σ[f ]

2πi v.p.

1

α+i

αi

e st F (s)ds =

1 2 (f(t ) + f(t + )),

f (t )

1 2 (f(t ) + f(t + )) = f (t) t f (t)

f (t + )

t

F (s)

f (t)

2πi

1

α+i

αi

e st F (s)ds.

s C F (s)

σ = Re(s) > σ 0

|F(s)| = O

k | ,

1

|s

s → ∞,

k > 1 lim |s| |F (s)||s k | = c > 0 α > σ 0

f(t) =

2πi

1

α+i

αi

e st F (s)ds

R α F

F (s)

F (s)

¯

F

F(s) = c

s +

¯

F(s),

F (s) =

s + 1 cos(t)

s 2

F (s)

F(s) 1 s

s → ∞

( k = 1).

F(s) =

s s 2 + 1 = 1

s + s 2 + 1 1

s

s = 1

s + s 2 s + 1)

2

1

s(s 2

= 1 s

1

s(s 2 + 1) .

H(t)

(sin H)(t) = +sin(τ ) H(tτ ) = t sin(τ )= 1cos(t)

0

0

t 0.

cos(t)

f (t)

f(t) =

2πi

1

α+i

α−∞

e st F (s)ds =

n

j=1

res(e st F(s), s j ),

s j e st F (s)

F (s)

F (s)

F(s) = A(s)

B(s) ,

A(s) B(s)

A(s)=a m s m +a m1 s m1 + ··· +a 0

B(s) = b n s n + b n1 s n1 + ··· + b 0

a

b

m

n

=

=

0,

0,

n 1 , n 2 , ··· , n r

n > m

s 1 , s 2 , ··· , s r B(s)

r

k=1

n k = n,

A(s k )

= 0,

k = 1, 2, · · · , r.

s k n k F

F(s) =

A(s)

B(s) =

r

n

k

k=1

j=1

a

(k)

j

(s s k ) j .

L[t j1

+

] = (j 1)!

s j

⇐⇒

L

(j 1)! =

t

j1

+

1

s

j

L

(j 1)! e s k t =

t

j1

+

1

(s s k ) j .

F (s)

f(t) =

r

n

k

k=1

j=1

(k)

j

a

1)! t j1

+

(j

e s k t .

n 1 = n 2 = ··· = n r = 1

f(t) =

n

k=1

a

(k